2008
DOI: 10.1016/j.rgg.2008.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical abrasion of kimberlite indicator minerals: experimental investigations

Abstract: The relative abrasive stability of kimberlite indicator minerals such as pyrope, picroilmenite, olivine, and apatite as well as diamonds and kimberlite fragments was studied experimentally, and the following sequence of mineral abrasive stability was established: pyrope–olivine–picroilmenite–apatite–kimberlite fragments. Diamond did not virtually change during the experiment. Kimberlite fragments appeared to be rather stable. Their relics were preserved until the end of the experiment, whereas the other minera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(11 citation statements)
references
References 1 publication
0
10
0
1
Order By: Relevance
“…Such minerals have been transported very short distances and are generally found within kimberlite eluvium and nearby aureoles [18][19][20]. The preservation of mineral intergrowths, kelyphitic rims, and inclusions is further evidence of the extremely limited transport distance and absence of mechanical abrasion of the grains.…”
Section: Morphologic Study Of Kimsmentioning
confidence: 98%
“…Such minerals have been transported very short distances and are generally found within kimberlite eluvium and nearby aureoles [18][19][20]. The preservation of mineral intergrowths, kelyphitic rims, and inclusions is further evidence of the extremely limited transport distance and absence of mechanical abrasion of the grains.…”
Section: Morphologic Study Of Kimsmentioning
confidence: 98%
“…5071Ë/4, ïðîáà 6) è â ñðåäíåì ñîñòàâëÿåò 11,11 êã/ò. Ïðåäñòàâëåí óãëîâàòûìè, óãëîâàòî-îêðóãëûìè, èçðåäêà îêðóãëûìè ç¸ðíàìè 0-I êëàññà ñîõðàííîñòè [1,4,8]. Ïîâåðõíîñòè ç¸ðåí øåðîõîâàòûå, ðåaeå ìàòèðîâàííûå, áóãîð÷àòûå.…”
Section: âåùåñòâåííûé ñîñòàâ êèìáåðëèòîâûõ ïîðîäunclassified
“…Regarding the question of the survival of diamonds during *300 km of transport along the Krishna River, recent studies on the relative abrasive stability of kimberlite indicator minerals such as pyrope, picroilmenite, olivine, apatite, diamonds, as well as kimberlite fragments, revealed that diamond is the most durable of them all and could survive long distances of transport (Afanasev et al 2008). Microdiamonds recovered recently in the beach placers of the Krishna-Godavari delta (Subrahmanyam et al 2005) could also have been derived from the RKF.…”
Section: Possible Source Of Alluvial Diamonds In the Krishna River Basinmentioning
confidence: 99%